Air Quality and Winter Heating: Some Evidence from China - Gao, Yannan; Sampattavanija, San (International Journal of Energy Economics and Policy, 2022)
This paper analyzes the effects of central winter heating prevailing in North China on air pollution level. Qin-Mountains and Huai-River borderline that distinguishes the heating and non-heating areas is considered to be a good quasi natural experiment. Regression discontinuity design as well as relevant robustness checks and placebo tests are combined to verify the effects. Distinctions of the effects regarding different groups of areas located in different latitudes are also taken into consideration. Finally, we find that central winter heating contributes to the growth of all major air pollutants of 17.62% on average between non- and heating seasons considering all important cities in heating areas in north China excluding the effects brought by other natural conditions like weather. As latitude increases, central heating contributes more to air pollution level. In the coldest areas, the contribution to the increase of winter air pollutants can reach more than 60% for PM2.5.